The Saknivka Plate: Scythian Iconography in the Imaging of Eschatological Concepts - Vertiienko, Hanna (Eikón / Imago, 2021)
This paper proposes the reconstruction of the Scythian eschatological concepts on the basis of semantics of the Sakhnivka plate composition (4th century BC, Museum of Historical Treasures of Ukraine, branch of the National Museum of History of Ukraine). Taking into account the ritual detour of the sacral center from left to right in the Indo-Iranian tradition, the plate plots show a consecutive visual statement of the episodes of the myth of Kolaxais’ destiny. The culmination scene of the plate includes three figures. The half-turned and full-face iconography of the Goddess shows her belonging to two figures, on her both sides: to a meeting of the bearded Scythian king on the right and a scene with a young Scythian on the left (an image of the young, “regenerated” king / Kolaxais). Only the last figure has a in caftan wrapped from right to left, i.e. the clasp of the “living person” (as opposed to other figures) that confirms his special status of ‘reborn’. Accordingly, scenes show the important episodes of the Scythian eschatological representations connected with posthumous fate, basis for the ideology of funerary rites.